Psychosocial Support and Quality of Life in CKD Patients on Hemodialysis Amidst the Sudan Conflict: A Cross-Sectional Study - Abdulsamad, Ahmed MohammedAlhassan Ismail; Hassan, Ibrahim Nagmeldin; Ibrahim, Mohamed (International Journal of Medical Students, 2025)
BACKGROUND: Chronic kidney disease (CKD) patients undergoing hemodialysis often experience significant physical and psychological challenges. The quality of life (QoL) for these patients is influenced by various factors, including psychosocial support (1). In conflict-affected regions like Sudan, the ongoing armed conflict has further complicated these challenges (2). This study aims to assess the impact of psychosocial support on the QoL of CKD patients on hemodialysis amidst the Sudan conflict and to evaluate how conflict-related disruptions affect their well-being. METHODS: We conducted a cross-sectional study involving 150 CKD patients on hemodialysis at two major hospitals in Khartoum, Sudan. Participants were selected through purposive sampling, ensuring diversity in demographics and clinical characteristics. We used standardized screening questionnaires, including the Kidney Disease Quality of Life-36 (KDQOL-36) for assessing QoL (3). Additional questions assessed psychosocial support levels and the impact of the Sudan conflict. We analyzed the data using SPSS version 26.0. We used descriptive statistics to measure the central tendencies and variability of demographic and clinical characteristics; we also used frequencies and percentages for psychosocial support levels and conflict-related factors among CKD patients. A p-value of 0.05 or less was considered statistically significant. RESULTS: Out of the 150 participants in the study, 60% were females and 40% were males, with a mean age of 55 ± 12 years. Most participants had been on dialysis for an average of 3.5 ± 2.1 years. Comorbidities included hypertension (70%), diabetes (40%), and cardiovascular disease (20%). Socioeconomic status varied, with 45% below the poverty line. The mean Quality of Life (QoL) scores were 55 ± 15 for physical health, 48 ± 17 for mental health, 52 ± 14 for social functioning, and 50 ± 16 overall. High emotional support was associated with significantly higher QoL scores (mean overall QoL 58 ± 12) compared to low emotional support (mean overall QoL 42 ± 15, p < 0.01). Strong social support correlated with better physical health (mean 60 ± 14 vs. 50 ± 16, p < 0.05) and overall QoL (mean 55 ± 13 vs. 45 ± 14, p < 0.01). Disrupted access to healthcare services was reported by 60% of participants, and 20% had been displaced due to the conflict. Disruption in healthcare access was linked to lower QoL scores (mean overall QoL 45 ± 17) compared to those with no disruptions (mean overall QoL 55 ± 15, p < 0.05). Displaced patients had poorer mental health scores (mean 42 ± 18) compared to non-displaced patients (mean 50 ± 16, p < 0.05). CONCLUSION: This study highlights the significant impact of psychosocial support on the QoL of CKD patients undergoing hemodialysis in conflict-affected settings. Higher levels of psychosocial support are associated with better QoL outcomes. The ongoing Sudan conflict amplifies the challenges faced by these patients, stressing the need for targeted psychosocial interventions and support systems to alleviate the adverse effects of the conflict on patient well-being. The findings call for implementing strategies to improve QoL and health outcomes for CKD patients in conflict zones.